Penguatan Pendidikan Kewarganegaraan Digital bagi Generasi Alpha dalam Menyongsong Masyarakat Society 5.0 - Syamzaimar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The rapid development of digital technology has transformed social life and given rise to Generation Alpha as a generation that grows up in a fully digitalized environment. In facing the Society 5.0 era, Generation Alpha is required not only to possess technological competencies but also to develop awareness, ethics, and responsibility as digital citizens. This study aims to analyze strategies for strengthening digital citizenship education for Generation Alpha in preparing for Society 5.0. The research employed a qualitative approach using a library research method. Data were collected from various scholarly sources, including journal articles, books, conference proceedings, and relevant documents discussing digital citizenship education, Generation Alpha, and Society 5.0. The data were analyzed using content analysis through data reduction, data display, and conclusion drawing. The findings reveal seven major strategies for strengthening digital citizenship education: (1) integrating digital citizenship into the curriculum, (2) implementing Project-Based Learning, (3) promoting the ethical use of Artificial Intelligence (AI), (4) strengthening information literacy and anti-hoax movements, (5) providing cybersecurity education, (6) reinforcing Pancasila values in digital spaces, and (7) fostering collaboration among schools, families, and digital communities. These strategies contribute to developing Generation Alpha's digital literacy, critical thinking skills, ethical awareness, and social responsibility in the use of technology. The study concludes that strengthening digital citizenship education is a strategic effort to prepare Generation Alpha to become intelligent, ethical, and responsible digital citizens who are ready to face the challenges of Society 5.0.